HERUS: the far-IR/submm spectral energy distributions of local ULIRGs and photometric atlas. Issue 2 (14th December 2017) - Clements, D L; Pearson, C; Farrah, D; Greenslade, J; Bernard-Salas, Jeronimo; González-Alfonso, E; Afonso, J; Efstathiou, A; Rigopoulou, D; Lebouteiller, V; Hurley, P D; Spoon, H
Abstract: We present the Herschel -SPIRE photometric atlas for a complete flux limited sample of 43 local ultraluminous infrared galaxies (ULIRGs), selected at 60 μm by IRAS, as part of the HERschel ULIRG Survey (HERUS). Photometry observations were obtained using the SPIRE instrument at 250, 350, and 500 μm. We describe these observations, present the results, and combine the new observations with data from IRAS to examine the far-infrared spectral energy distributions (SEDs) of these sources. We fit the observed SEDs of HERUS objects with a simple parametrized modified blackbody model, where temperature and emissivity β are free parameters. We compare the fitted values to those of non-ULIRG local galaxies, and find, in agreement with earlier results, that HERUS ULIRGs have warmer dust (median temperature T = 37.9 ± 4.7 K compared to 21.3 ± 3.4 K) but a similar β distribution (median β = 1.7 compared to 1.8) to the Herschel reference sample (HRS, Cortese et al. 2014 ) galaxies. Dust masses are found to be in the range of 10 7.5 –10 9 M⊙, significantly higher than that of HRS sources. We compare our results for local ULIRGs with higher redshift samples selected at 250 and 850 μm. These latter sources generally have cooler dust and/or redder 100-to-250 μm colours than our 60 μm-selected ULIRGs. We show that this difference may in part be the result of the sources being selected at different wavelengths rather than being a simple indication of rapid evolution in the properties of the population.